Applied palaeontology - Jones, Robert Wynn (Cambridge : Cambridge University Press, 2006)
This book was first published in 2006. Palaeontology has developed from a descriptive science to an analytical science used to interpret relationships between earth and life history. Applied Palaeontology adopts a holistic, integrated approach to palaeontology, highlighting its key role in the study of the evolving earth, life history and environmental processes. After an introduction to fossils and their classification, each of the principal fossil groups are studied in detail, covering their biology, morphology, classification, palaeobiology and biostratigraphy. The latter sections focus on the applications of fossils in the interpretation of earth and life processes and environments. It concludes with case histories of how our knowledge of fossils is applied, in industry and elsewhere. This is a valuable reference for anyone involved in the applications of palaeontology, including earth, life and environmental scientists, and petroleum, minerals, mining and engineering professionals.
Title from publisher's bibliographic system (viewed on 17 Sep 2019).
Keywords: elektronické knihy; electronic books; Paleontology